Gender-Inclusive Fellowship Naming and Equity, Diversity, and Inclusion in Radiology: An Analysis of Radiology Department Websites in Canada and the United States. Issue 3 (August 2022) - Yan, Tyler D.; Mak, Lauren E.; Carroll, Evelyn F.; Khosa, Faisal; Yong-Hing, Charlotte J.
Purpose: Transgender and gender non-binary (TGNB) individuals face numerous inequalities in healthcare and there is substantial work to be done in fostering TGNB culturally competent care in radiology. A radiology department's online presence and use of gender-inclusive language are essential in promoting an environment of equity, diversity, and inclusion (EDI). The naming of radiology fellowships and continuing medical education (CME) courses with terminology such as "Women's Imaging" indicates a lack of inclusivity to TGNB patients and providers, which could result in suboptimal patient care.Methods: We conducted a cross-sectional analysis of all institutions in Canada and the United States (US) offering training in Breast Imaging, Women's Imaging, or Breast and Body Imaging. Data was collected from each institution's radiology department website pertaining to fellowship names, EDI involvement, and CME courses.Results: 8 Canadian and 71 US radiology fellowships were identified. 75% of Canadian and 90% of US fellowships had gender-inclusive names. One (12.5%) Canadian and 29 (41%) US institutions had EDI Committees mentioned on their websites. Among institutions publicly displaying CME courses about breast/body or women's imaging, gender-inclusive names were used in only 1 (25%) of the Canadian CME courses, compared to 81% of the US institutions.Conclusions: Most institutions in Canada and the US have gender-inclusive names for their radiology fellowships pertaining to breast and body imaging. However, there is much opportunity to and arguably the responsibility for institutions in both countries to increase the impact and visibility of their EDI efforts through creation of department-specific committees and CME courses.